Faktor-Faktor Yang Mempengaruhi Volume Pembiayaan Berbasis Bagi Hasil Pada Perbankan Syariah Di Indonesia - Tri Widiastuty (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This research was conducted to prove how much do profitability, inflation rate, and non performing financing give effect to volume of profit and loss sharing based- financing that observed from Shariah banks annual report. This research is expected to provide benefits for the development of Sharia accounting knowledge, especially related to Islamic banking financing products. In addition, this research is also expected to provide input for management of Islamic banks to determine the factors that may effect to volume of profit and loss sharing based- financing and to give information for investors that can be used as the basis for a decision to invest in Islamic banks. Sample selection method used in this research is purposive sampling method. Sample in this research are 10 Islamic banks in Indonesia with the research period ranging from 2003 to 2014. The data analysis method used in this research is multiple regression analysis. The results of this research indicate that profitability doesn’t have a positive effect to volume of profit and loss sharing based- financing, inflation rate doesn’t have a negative effect to volume of profit and loss sharing based- financing, and non performing financing doesn’t have a negative effect to volume of profit and loss sharing based- financing.